Global, regional, and national quality of care of gallbladder and biliary tract cancer: a systematic analysis for the global burden of disease study 1990-2017 - Javad Khanali; Mohammad-Reza Malekpour; Mohammadreza Azangou-Khyavy; Sahar Saeedi Moghaddam; Negar Rezaei; Ali-Asghar Kolahi; Mohsen Abbasi-Kangevari; Esmaeil Mohammadi; Nazila Rezaei; Moein Yoosefi; Mohammad Keykhaei; Yosef Farzi; et al. (BMC, 2021)
Abstract Background To improve health outcomes to their maximum level, defining indices to measure healthcare quality and accessibility is crucial. In this study, we implemented the novel Quality of Care Index (QCI) to estimate the quality and accessibility of care for patients with gallbladder and biliary tract cancer (GBBTC) in 195 countries, 21 Global Burden of Disease (GBD) regions, Socio-demographic Index (SDI) quintiles, and sex groups. Method This cross-sectional study extracted estimates on GBBTC burden from the GBD 2017, which presents population-based estimates on GBBTC burden for higher than 15-year-old patients from 1990 to 2017. Four secondary indices indicating quality of care were chosen, comprising Mortality to incidence, Disability-Adjusted Life Year (DALY) to prevalence, prevalence to incidence, and years of life lost (YLL) to years lived with disability (YLD) ratios. Then, the whole dataset was analyzed using Principal Component Analysis to combine the four indices and create a single all-inclusive measure named QCI. The QCI was scaled to the 0-100 range, with 100 indicating the best quality of care among countries. Gender Disparity Ratio (GDR) was defined as the female to male QCI ratio to show gender inequity throughout the regions and countries. Results Global QCI score for GBBTC was 33.5 in 2017, which has increased by 29% since 1990. There was a considerable gender disparity in favor of men (GDR = 0.74) in 2017, showing QCI has moved toward gender inequity since 1990 (GDR = 0.85). Quality of care followed a heterogeneous pattern among regions and countries and was positively correlated with the countries' developmental status reflected in SDI (r = 0.7; CI 95%: 0.61-0.76; P value< 0.001). Accordingly, High-income North America (QCI = 72.4) had the highest QCI; whereas, Eastern Sub-Saharan Africa (QCI = 3) had the lowest QCI among regions. Patients aged 45 to 80 had lower QCI scores than younger and older adults. The highest QCI score was for the older than 95 age group (QCI = 54), and the lowest was for the 50-54 age group (QCI = 26.0). Conclusions QCI improved considerably from 1990 to 2017; however, it showed heterogeneous distribution and inequity between sex and age groups. In each regional context, plans from countries with the highest QCI and best gender equity should be disseminated and implemented in order to decrease the overall burden of GBBTC.